Diversity in marketing practice - Torres, Ann Marie (Trinity College (Dublin, Ireland). Trinity Business School, 2009)
Theory development in marketing has received periodic debate. In the spirit of reappraisal, this thesis endeavours to explain the nature of diversity in marketing practice found among firms and the manner in which marketing practice is related to organisational performance. The specific research goals are to explore: the nature of diversity in marketing practice, as linked to strategic archetypes; whether there is evidence of order in the diversity of marketing practice that can be linked to organisational performance; and the nature of the relationships among strategy, structure, and marketing practice and their impact on organisational performance.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin